State and local intelligence in the war on terrorism - Riley, Kevin Jack, 1964- (RAND Corp., 2005)
One aspect of combating terrorism that is often discussed but seldom examined in detail concerns the overlap of intelligence and law enforcement and the role of state and local law enforcement agencies as the ultimate "eyes and ears" in the war on terrorism. This report helps fill that gap by examining how state and local law enforcement agencies conducted and supported counterterrorism intelligence activities after 9/11. It analyzes data from a 2002 survey of law enforcement preparedness in the context of intelligence and reports the results of case studies showing how eight local law enforcement agencies handle intelligence operations. Finally, it suggests ways that the job of gathering and analyzing intelligence might best be shared among federal, state, and local agencies.